Construction of an Escherichia coli expression vector for the non-structural (NS)-1 protein of avian influenza virus H5N1 - Agusta, Istiqomah; Jacinta Santhanam,; Yap, Wei Boon (Penerbit Universiti Kebangsaan Malaysia, 2020)
In the search for universal vaccine candidates for the prevention of avian influenza, the non-structural (NS)-1 protein 1 of avian influenza virus (AIV) H5N1 has shown promising potential for its ability to effectively stimulate the host immunity. This study was aimed to produce a bacterial expression plasmid using pRSET B vector to harbour the NS1 gene of AIV H5N1 (A/Chicken/Malaysia/5858/2004 (H5N1)) for protein expression in Escherichia coli (E. coli). The NS1 gene (687 bp) was initially amplified by polymerase chain reaction (PCR) and then cloned into a pGEM-T Easy TA vector. The NS1 gene was released from pGEM-T-NS1 using EcoRI and XhoI restriction enzymes (RE). The pRSET B vector was also linearized using the same RE. The digested NS1 gene and linearized pRSET B were ligated using T4 DNA ligase to form the expression plasmid, pRSET B-NS1. The NS1 gene sequence in pRSET B-NS1 was confirmed by DNA sequencing. To prepare recombinant bacterial cells for protein expression in the future, pRSET B-NS1 was transformed into E. coli strain BL21 (DE3) by heat-shock. Colonies bearing the recombinant plasmid were screened using PCR. The DNA sequencing analysis revealed that the NS1 gene sequence was 97% homologous to that of AIV H5N1 A/Chicken/Malaysia/5858/2004 (H5N1). These results indicated that the NS1 gene of influenza A/Chicken/Malaysia/5858/2004 (H5N1) was successfully amplified and cloned into a pRSET B vector. Bacterial colonies carrying pRSET B-NS1 can be used for the synthesis of NS1-based influenza vaccine in the future and thereby aid in the prevention of avian influenza.